Training Does Not Always Improve Performance: The Mediating Role of Competence and Commitment among Civil Servants in Papua - Joko Waluyo; Yohanis Rante; Westim Ratang; Jack H Syauta (PT Inovasi Pratama Internasional, 2026)
Training is often assumed to directly improve employee performance, yet this assumption may not hold without the role of intervening variables. This study examines the effect of training and work motivation on employee performance, both directly and indirectly through competence and commitment, among civil servants in a region with geographical challenges. A quantitative approach was applied using Structural Equation Modeling (SEM) with AMOS. The sample comprised 213 administrative training alumni of the Religious Training Center of Papua from seven Offices of the Ministry of Religious Affairs, with significance criteria of CR ≥ 1.96 or p ≤ 0.05. The results show that training significantly affects competence (CR 5.093) and commitment (CR 4.694) but has no direct effect on performance (CR 1.870; p 0.061). Work motivation significantly affects competence, commitment, and performance. Competence and commitment each significantly affect performance and mediate the effects of both training and motivation on performance, with commitment as the most dominant mediator. The model explains 48.3% of the variance in employee performance. These findings confirm that training does not automatically improve performance but requires strengthening competence and commitment as prerequisites. Accordingly, improving civil servant performance demands post-training support, job rotation, and commitment reinforcement rather than merely conducting training